Optimal combination treatment regimens of vaccine and radiotherapy augment tumor-bearing host immunity - Fayun Zhang (Nature Portfolio, 2021)
Zhang et al. use mouse tumor models to show that the optimum treatment regime for Treg-induced radiation resistance is vaccine administration followed by radiation therapy. This finding could inform the design of future combinatorial cancer therapies in the clinic.